Deposition of SnS thin films on various substrates at room temperature - N Aparna; Reshma S Philip; Meril Mathew (Applied Surface Science Advances, 2023)
This study describes a modified SILAR technique for depositing Tin monosulphide (SnS) thin films on diverse substrates, such as glass, ITO coated glass, and OHP sheet, all at room temperature. This simple, less expensive, environmentally friendly, and industrially scalable method allows excellent control over the deposition rate and thickness, as well as many experimental flexibilities. The advantages of depositing films at room temperature include energy efficiency, cost-effectiveness, and suitability for heat-sensitive materials. The deposited SnS thin films underwent comprehensive analysis through XRD, FESEM, EDAX, XPS, TGA, and UV–visible spectroscopy to thoroughly understand their properties. The results showed that the films were polycrystalline, orthorhombic, single-phase, and nearly stoichiometric, with a bandgap value in the visible region. The deposition conditions were optimized to achieve high-quality thin films, and the impact of substrate variations on film characteristics was also investigated. The study showcased the simplicity of doping in the modified SILAR process. Furthermore, the study demonstrated the photocatalytic degradation effectiveness of SnS thin films against the dye Rhodamine B. Various analyses, including UV-visible spectroscopy studies, ROS scavenger tests, ROS indicator tests, and kinetic analysis, were performed. The photodegradation process was effectively described by the Langmuir-Hinshelwood (L-H) mechanism.